IMPROVED STUDENT INTEREST AND UNDERSTANDING OF MATERIAL CONTENT SERVICES THROUGH CONTROL METHOD OF GAME IN DISTRICT Prembun SMP Negeri 1 Kebumen - Cahyati, Khristiana Tri (Universitas Muhammadiyah Metro, 2015)
Abstract: Interest is the motivating force that will encourage students to get excited and remember what she learned. The learning process is less qualified, inefficient and lacked the appeal, and even tend to be boring, causing low student interest. This study aims to determine the increase in interest and understanding students' mastery of content Counseling services through a game method in class VII A Prembun SMP Negeri 1 Kebumen district. This research is a classroom action research conducted in two cycles. Techniques of data retrieval from the scale of interest, observation, evaluation, documentation and interviews. Data analysis with comparative descriptive technique. Indicators of success: 1) Active engagement in the learning process well, the range of 60-80%, 2) increase student interest, and 3) Obtaining a new understanding of at least 85%. The results showed the service mastery of content game method can be: 1) increasing student interest of 76.01 (pre-cycle) to 84.50 (first cycle) and 84.17 (second cycle), 2) improving the understanding of students to 93% (cycle I) and 93.5% ( cycle II).Keywords: interest, understanding, mastery of content services, methods of a game.